2020
DOI: 10.1111/jors.12480
|View full text |Cite
|
Sign up to set email alerts
|

Investigating space‐time patterns of regional industrial resilience through a micro‐level approach: An application to the Italian wine industry

Abstract: This paper introduces a new methodology to identify space‐time patterns of regional resilience using a micro‐level approach. The novel empirical tool combines geographically weighted regression with panel stochastic frontier analysis with endogenous covariates. The analysis is implemented on a panel of farm holdings operating in the Italian wine industry, focusing on the impact of a major institutional change. The results show the effectiveness of the new procedure in identifying geographical clusters of wine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 97 publications
1
8
0
Order By: Relevance
“…The results suggest that there is room for improvements at both firm-level and country-wide levels. From a managerial point of view, firms should reassess their input management relationship, specifically, developing supplier relationships, generating economies of scale, and en- Structurally, the results show that there is a need for a long-term strategy of the industry, which calls for the design of policies that allow firms to penetrate new markets (exports) and boost the value of their product in the international competitive scenario, which is in line with the findings of Canello & Vidoli (2020). These policies should consider the specificities of firms within the industry (due to high heterogeneity) since firms benefit differently from support policies according to their characteristics (Náglova & Pechrová, 2019), such as the wine region where they are located (Canello & Vidoli, 2020).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The results suggest that there is room for improvements at both firm-level and country-wide levels. From a managerial point of view, firms should reassess their input management relationship, specifically, developing supplier relationships, generating economies of scale, and en- Structurally, the results show that there is a need for a long-term strategy of the industry, which calls for the design of policies that allow firms to penetrate new markets (exports) and boost the value of their product in the international competitive scenario, which is in line with the findings of Canello & Vidoli (2020). These policies should consider the specificities of firms within the industry (due to high heterogeneity) since firms benefit differently from support policies according to their characteristics (Náglova & Pechrová, 2019), such as the wine region where they are located (Canello & Vidoli, 2020).…”
Section: Resultssupporting
confidence: 72%
“…The total annual value of turnover is considered as output (Kallas & Lambarra, 2010). As inputs, the traditional factors labor and capital (Canello & Vidoli, 2020) are included through the number of employees and the value of annual depreciation and amortizations of capital. Additionally, we include the cost of raw materials (CRM), which includes the cost of grapes, 2019).…”
Section: Datamentioning
confidence: 99%
“…This paper hints at the need to design specific spatial policies for each wine region in which all competitive advantages should be exploited, and on the other hand, the individual limitations should be mitigated, as suggested by Canello and Vidoli (2020), for the Italian wine industry. Furthermore, the relatively new competitive environment of the Portuguese wine industry calls for the development of policies that support collective added value for the industry as a means to reach competitive and industry-wide efficiency gains.…”
Section: Discussionmentioning
confidence: 99%
“…Outreville (2016) found spatial spillovers in the wine industry and that the location can determine the level of efficiency of wine firms. Additionally, Canello and Vidoli (2020) observed the existence of geographical clusters. Bravo-Ureta et al (2020), focusing on grape growers, showed that the geographic location influences productive efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation